Different Imaging Features of Retroperitoneal Unicentric Castleman's Disease: A Case Report - Cao, Yonghong (Case Rep Oncol, 2020)
Castleman's disease is a rare disease which is difficult to diagnose early due to its lack of specific manifestations, and also is easily confused with lymphoma or other solid tumors. Castleman's disease can occur in any part of the body containing lymph nodes and is most common in the chest, followed by the neck, abdomen, and axillae. A 37-year-old woman was admitted to our hospital because of a tumor near the adrenal gland found by computed tomography. Positron emission tomography-computed tomography revealed that the retroperitoneal tumor may be a malignant disease. However, the pathological diagnosis after laparoscopic resection was retroperitoneal Castleman's disease, hyaline vascular type.